Good Corporate Governance dan Manajemen Keuangan dalam Ekonomi Syariah - Manunggal, Syafrudin Arif marah (IAIN Salatiga, 2013)
The Good Corporate Governance (GCG) facing challenges to Islamic banks nowadays not only in Indonesia but also in the entire world. GCG is necessary to the Islamic banks due to significance of the stakeholders trust towards Islamic banks its self. But in practice, the GCG could serve as an obligatory and formal instrument for delivering transparant public financial reports of the Islamic banks. In avoiding its shortage of application, Islamic finance management gives guide for encountering the formalistic condition of the GCG of the Islamic banks. For the GCG and the Islamic financial management both are very important, this paper discusses a likely convergence between both principle. Finally, the GCG has to be applied by guiding the Islamic financial management. The Islamic financial management is something to do with weather the religious normative assumptions and social economic ones.